Desempenho de um sistema composto por um filtro anaeróbio e um 'wetland' horizontal na produção de água para reúso predial a partir de água cinza clara - Knupp, Andrielly Moutinho (2013)
The wetlands have been shown as a favorable option for the greywater treatment aiming the building reuse due to the good pollutants removal, and mainly, the low cost of implantation and operation, as well as minimal environmental impact when compared with another systems. The present study aimed to characterize physico-chemical and microbiologically the light greywater generated in a corporate building; evaluate the performance of horizontal wetland (HW) as a post-treatment of an upflow anaerobic filter (AF) treating light greywater in the water reuse building production; and to study the application of the Analytic Hierarchy Process (AHP) as assistance tool in the selection of the macrophyte to be used at the evaluated wetland. The physico-chemical and microbiological analysis were performed according the Standard Methods for Examination of Water and Wastewater. The greywater s volume generated in the corporate building was 103,1 L.p.d-1. According with the characterization of the light greywater, the pH showed a high value (9.0), significant presences of turbidity (50.9 TU), TSS (44.8 mg.L-1), organic matter (178.3 mgO2.L-1 COD and 41.3 mgO2.L-1 DBO5,20), SO42- (60.1 mg.L-1) and microorganisms (2.2x104 NMP.100mL-1 total coliforms and 2.0x102 NMP.100mL-1 E. coli), in addition of low nitrogen and phospohrous concentrations. Note that the greywater evaluated has a ratio DBO5,20/DQO ranging 0.2 at 0.3, and that despite the low biodegradability, the biological treatment is still possible, but under limitant degradation conditions. About the performance of greywater treatment system, were analyzed four periods of experiments, being characterized by the hydraulic retention time (HRT) of 0.7; 1.0; 1.9 e 3.2 days. Such as result, observed that the HW effluent showed better performance for the HRT of 3.2 days over the analyzed periods, making it adequate when used such as post-treatment of an anaerobic filter. Were achieved global removal efficiencies mean of 80% to turbidity and total suspended solids. Moreover, was reached too removal efficiencies of 81% COD and 66% BOD5,20. The mean density obtained of E. coli in the HW effluent was 3.1x10² NMP.100mL-1. The AHP was executed in three steps: identification of the macrophytes used at the wetlands, selection of ten more macrophytes used in this treatment type and application of the AHP method to the Greater Victoria s Region conditions. As result of the AHP application, obtained the Equisetum hyemale L. and Canna x generalis such as the more appropriate plants to the greywater treatment by wetlands.